The Impact of Payroll Tax Reductions on Employment and Wages: A Natural Experiment Using Firm Level Data - Maarten Goos; Jozef Konings (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
Past evidence on the incidence of payroll tax subsidies on employment and wages for disadvantaged workers has been quite mixed. Therefore, this paper makes use of a unique panel of firm level data and a natural experiment to analyze the incidence of wage subsidies on full-time manual workers and pre-tax wages. Using a number of straightforward evaluation estimators we find that employment subsidies increased full-time manual employment and pre-tax wages. Moreover, we find that employment subsidies have increased employment but not wages by more in low-wage exporting industries. This is line with a textbook description of labor markets where it is predicted that the incidence of employment subsidies on employment and wages is larger the more elastic is product and therefore labor demand and where the employment effect is larger and the wage effect is smaller the more elastic is labor supply because of a binding minimum wage.
Keywords: 330; Lohnsummensteuer; Steuersenkung; Beschäftigungseffekt; Lohnniveau; Schätzung; Europa